1976
DOI: 10.1029/ja081i001p00111
|View full text |Cite
|
Sign up to set email alerts
|

Helium isotopes in an aurora

Abstract: Aluminum and platinum foils were flown into two bright auroras and subsequently recovered. They were then analyzed for traces of trapped noble gases in a sensitive high‐resolution mass spectrometer. In this paper we report the detection of ³He and confirm measurements of the 4He flux reported in a previous paper. The 4He∶³He ratio in the first (brighter) aurora was 2950 ± 250. This ratio is only slightly higher than the average solar wind ratio of 2350 and since the atmospheric ratio is grossly different (250 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This air, locally mixed with air downward, may tentatively produce a high 3 He/ 4 He ratio. This mechanism is associated with the formation of auroras and is called Auroral Helium Precipitation (Buhler et al, 1976), and it may explain excess 3 He observed in this work. Other sources include the decay of tritium produced by nuclear weapons and nuclear reactors, but it is thought to be negligible in amount (Lupton and Evans, 2004).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This air, locally mixed with air downward, may tentatively produce a high 3 He/ 4 He ratio. This mechanism is associated with the formation of auroras and is called Auroral Helium Precipitation (Buhler et al, 1976), and it may explain excess 3 He observed in this work. Other sources include the decay of tritium produced by nuclear weapons and nuclear reactors, but it is thought to be negligible in amount (Lupton and Evans, 2004).…”
Section: Discussionmentioning
confidence: 68%
“…1.5 × 10 14 atoms/cm 2 (Ozima and Podosek, 1983), it would result in a flux of 190 atoms/cm 2 sec. This value is about 40 times greater than the steady state auroral precipitation flux of 5 atoms/cm 2 sec (Buhler et al, 1976). In other words, even if a solar flare of this scale were to occur once every two years, it would be 20 times larger than the normal auroral precipitation flux.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, the helium in the solar wind is primarily doubly charged while that in the ionosphere is singly charged. Biihler et al (1972Biihler et al ( , 1976 and Axford et al (1972) measured helium isotopes and derived the 3He/4He ratio in aurora by exposing foils to particle fluxes on two rocket flights. The foils were recovered and were subsequently analyzed by heating them in the source of a laboratory mass spectrometer.…”
Section: Introductionmentioning
confidence: 99%
“…Such an experiment was later on carried out during the Apollo 11 and 12 missions, when aluminum foils (mounted on a pole stuck in the lunar soil) were exposed to flux of solar wind particles from the surface of the Moon [11]. In 1972 the foil sampling technique was used again to measure the noble gas fluxes in the auroral primary radiation [12,13]. This time aluminum and platinum foils were mounted on two Nike-Tomahawk rockets that were launched directly into bright auroras.…”
Section: The Foil Collection Technique: the Collisa Experiments On Mirmentioning
confidence: 99%